Macroprudential capital buffers in heterogeneous banking networks: Insights from an ABM with liquidity crises - Andrea Gurgone; Giulia Iori (Bamberg University, Bamberg Economic Research Group (BERG), 2020)
To date, macroprudential policy inspired by the Basel III package is applied irrespective of the network characteristics of the banking system. We study how the implementation of macroprudential policy in the form of additional capital requirements conditional to systemic-risk measures of banks should regard the degree of heterogeneity of financial networks. We adopt a multi-agent approach describing an artificial economy with households, firms, and banks in which occasional liquidity crises emerge. We shape the configuration of the financial network to generate two polar worlds: one is characterized by few banks who lend most of the credit to the real sector while borrowing interbank liquidity. The other shows a higher degree of homogeneity. We focus on a capital buffer for SII and two buffers built on measures of systemic impact and vulnerability. The research suggests that the criteria for the identification of systemic-important banks may change with the network heterogeneity. Thus, capital buffers should be calibrated on the heterogeneity of the financial networks to stabilize the system, otherwise they may be ineffective. Therefore, we argue that prudential regulation should account for the characteristics of the banking networks and tune macroprudential tools accordingly.
Keywords: C63; D85; E44; G01; G21; 330; agent-based model; capital requirements; capital buffers; financial networks; macroprudential policy; systemic-risk